Strategi Edukasi Interaktif untuk Meningkatkan Pengetahuan dan Kepatuhan Pendamping Minum Obat Tuberkulosis - Ade, Mujaidin; Ardian, Iwan; Setyowati, Wahyu Endang (FORIKES, 2025)
The success of tuberculosis therapy depends heavily on the role of medication companions in ensuring that patients undergo treatment regularly and completely. The objective of this study was to comprehensively identify various effective interactive educational strategies to improve knowledge and adherence of medication companions in tuberculosis treatment. This study was a systematic literature review. Literature was obtained from four databases: PubMed, Scopus, ProQuest, and Google Scholar using the keywords